2018
DOI: 10.1071/mf17350
|View full text |Cite
|
Sign up to set email alerts
|

Life history characteristics of the potentially invasive Ponto-Caspian goby Neogobius fluviatilis in natural lakes from its native range (Black Sea region of Turkey)

Abstract: The aim of this study was to provide baseline data and fill an outstanding knowledge gap in our understanding of factors affecting the invasiveness of the Ponto-Caspian gobiid Neogobius fluviatilis. To this end, the life history traits (as somatic growth and reproduction) of N. fluviatilis were studied in three natural freshwater lakes in its native range. These populations were characterised by slow somatic growth rates, being the slowest reported across all the native and non-native ranges of N. fluviatilis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…In the present study, gut content analysis of P. semilunaris and N. fluviatilis from some natural lakes within both species’ native range revealed overall similarities in prey consumption, with dietary overlap evident during the spawning period (Karakuş et al, ; Top et al, ). Previous studies on the diet of N. fluviatilis consistently indicate that this gobiid consumes a broad spectrum of prey items, which in its nonnative range consist mainly of macroinvertebrates (i.e., Amphipoda, Bivalvia, Chironomidae, Odonata, and Trichoptera; Adámek et al, ; Grabowska et al, ; Kakareko et al, ; Piria et al, ), and in its native range of Bivalvia, Chironomidae and other insects, Crustacea, Oligochaeta, Polychaeta, Mollusca, as well as fish eggs and small fish (i.e., Black Sea and Sea of Azov basins; Abdoli, Rahmani, & Rasooli, ; Gaygusuz et al, ; Pinchuk et al, ; Smirnov, ).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…In the present study, gut content analysis of P. semilunaris and N. fluviatilis from some natural lakes within both species’ native range revealed overall similarities in prey consumption, with dietary overlap evident during the spawning period (Karakuş et al, ; Top et al, ). Previous studies on the diet of N. fluviatilis consistently indicate that this gobiid consumes a broad spectrum of prey items, which in its nonnative range consist mainly of macroinvertebrates (i.e., Amphipoda, Bivalvia, Chironomidae, Odonata, and Trichoptera; Adámek et al, ; Grabowska et al, ; Kakareko et al, ; Piria et al, ), and in its native range of Bivalvia, Chironomidae and other insects, Crustacea, Oligochaeta, Polychaeta, Mollusca, as well as fish eggs and small fish (i.e., Black Sea and Sea of Azov basins; Abdoli, Rahmani, & Rasooli, ; Gaygusuz et al, ; Pinchuk et al, ; Smirnov, ).…”
Section: Discussionsupporting
confidence: 49%
“…Using a Euclidean distance measure following normalization of the data, these were used to obtain a distance matrix, which was subjected to 9,999 permutations of the raw data and tested for significance, with a posteriori pairwise comparisons evaluated at α = 0.10 for heuristic purposes (Kline, ). To assess ontogenetic variation in feeding, both species were divided into two groups (adult and juvenile) based on size at maturity for P. semilunaris (Top, Karakuş, Tepeköy, Britton, & Tarkan, ) and N. fluviatilis (Karakuş et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generation time is widely used as an indicator for invasion risk assessment (Rosecchi, Thomas, & Crivelli, ). Short generation is regarded as one of the key life history traits that associate with high invasion risk for various vertebrate groups, including fishes (Olden et al, ), birds (Jeppsson & Forslund, ) and mammals (Davidson, Hamilton, Boyer, Brown, & Ceballos, ).The lifespan of goby fish varies greatly among species, ranging from 1 year for the Eucyclogobius newberryi (Swcnson, ) to 7 years for the Neogobius fluviatilis (Karakuş, Karakuş, Tepekoy, Britton, & Tarkan, ). In present study, otolith based age determination showed that T. cirratus in the Chaohu Lake was a short‐lived species as the oldest individual was 3+ years old while most individuals were in age 1+ and 2+ group and only 6.2% individuals were in age 3+ group.…”
Section: Discussionmentioning
confidence: 99%